JCM-Advances in Cardiology - Henein, Michael (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Cardiology and cardiovascular sciences are two rapidly growing areas in medicine, with heart diseases being the number one cause of death worldwide. The last four decades have witnessed many developments in various cardiological sciences, including coronary artery disease, valve disease, heart failure, congenital heart diseases, and cardiovascular imaging, with a number of newly developed concepts, such as cardio-oncology, cardio-renal diseases, and preventive cardiology. This Special Issue (SI) of the Journal of Clinical Medicine, entitled "JCM-Advances in Cardiology", focuses on recent advances in the cardiological sciences. It published 8 research articles of significant clinical and scientific value.